Carbamazepine-viloxazine interaction in patients with epilepsy. Issue 10 (October 1986) - Pisani, F; Fazio, A; Oteri, G; Perucca, E; Russo, M; Trio, R; Pisani, B; Di Perri, R
Abstract : In six depressed epileptic patients stabilised on carbamazepine therapy, addition of the antidepressant agent viloxazine (300 mg/day for three weeks) induced a marked (average 55%) increase in steady-state plasma carbamazepine concentration. The concentration of the active metabolite carbamazepine-10, 11-epoxide also increased during viloxazine therapy, but to a lesser extent (16%). In three patients, these effects were associated with symptoms of carbamazepine intoxication, which regressed rapidly when plasma carbamazepine and carbamazepine-10, 11-epoxide levels returned to baseline values after discontinuation of viloxazine. In a seventh patient, viloxazine had to be discontinued after only two weeks because of severe side effects associated with a striking elevation of carbamazepine and carbamazepine 10, 11-epoxide levels (by 197% and 137% respectively). Although viloxazine appears to be one of the few antidepressants which can be used safely in patients with epilepsy these results indicate that the drug should be prescribed with great caution in subjects treated with carbamazepine. The mechanism of the interaction probably involves inhibition of the metabolism of both carbamazepine and its active epoxide metabolite.